(untitled) (Research, Society and Development, 2021)
The aim of the study is to identify nursing care for the prevention and management of hypertension in pregnant women in primary care. Integrative literature review. The search was conducted in the LILACS, MEDLINE, SCIELO databases, via the Capes periodicals portal with the Mesh "Hypertension, pregnancy-induced" OR "prenatal care" OR "primary care nursing". The initial sample contained a total of 52,595 articles. After using the inclusion and exclusion criteria, a total of 39,997 studies were obtained and after reading the titles and abstracts, a final sample of 1,345 studies was obtained. After analyzing the publications, it was observed the importance of nursing care during prenatal care, as well as the qualification of professionals in the appropriate management of hypertensive pregnant women and, therefore, in the prevention of possible complications, which should have a positive impact on reducing maternal and infant mortality rates. The significant percentage of young women with hypertension during pregnancy, as well as the existence of risk factors among these women, was evident in the study. It is necessary the nursing interventions involving the control of hypertension, reception, emotional and spiritual upport for pregnant women and their families, and the development of strategies that can contribute to reducing anxiety and stress, and encouragement of physical activity, guidance on the use of medications, control and monitoring of body weight and nutritional control.